Interaction Between Animal Burrowing and Loess Cave Formation in the Chinese Loess Plateau - Geng, Haopeng; Liu, Ru; Zheng, Weishan; Zhang, Yunbo; Xie, Rong; Guo, Yu; Pan, Baotian (Frontiers in Earth Science, 2021)
Although the interactions between biotic and geomorphic processes usually occur on small spatial and short temporal scales, many of the mechanisms remain to be investigated. This study provides the first direct evidence of the interaction between biotic burrowing and loess cave formation in the Chinese Loess Plateau (CLP). The study area is the Qingshui Valley in the western CLP, near Lanzhou. We surveyed the target site (with an area of ~13,367 m2) four times from Jul 2019 to Dec 2020, using an unmanned aerial vehicle (UAV). High resolution UAV images enabled us to determine the temporal and spatial dynamics of biotic burrowing and loess caves. The results show that loess caves tended to develop down valley below collapses, while animal burrows were preferentially located upslope away from collapses. Despite the distinct “topographic niches” for both biotic and abiotic processes, we observed an interaction between the two processes in space when tracking their temporal dynamics. Three out of seven new loess caves were in the process of formation at typical “topographic niches” of animal burrows and there was a significantly high animal burrow density around these three caves before their initiation. These results indicate that the three caves were directly initiated from animal burrows and/or developed under the influence of biotic activities. Therefore, biotic burrowing promotes the spatial heterogeneity of loess cave distribution. We also found significant decreases in animal burrow density surrounding the newly-formed loess caves after their initiation. This may reflect a risk avoidance strategy of animal burrowing, which causes animals to avoid areas of recent mass movement (i.e., collapses and new caves). The formation and expansion of loess caves can dictate the distribution of active areas of biotic disturbance. Our results demonstrate a clear interaction between biotic burrowing and loess cave formation, and they emphasize the role of biological agents as a mechanism for the formation of loess caves, which enrich the understanding of searching fingerprints of life during landscape evolution.